Clinical value of tissue velocity imaging technique in evaluating left ventricular structure and function in patients with type 2 diabetic end-stage renal disease undergoing hemodialysis - Zhang Li; Jiang Li-na; Zhao Na; Wu Li-fei (Linchuang shenzangbing zazhi)
Objective To explore the clinical value of tissue velocity imaging technique in evaluating left ventricular structure and function in patients with type 2 diabetic end-stage renal disease undergoing hemodialysis.Methods A total of 206 patients with end-stage renal disease with type 2 diabetes from May 2018 to October 2019 were selected as observation subjects.According to the different stages of renal replacement therapy, they were divided into two groups of non-hemodialysis（n=95）and hemodialysis（n=111）.At the same time, 80 healthy volunteers for physical examination in the same period were selected as control group（n=80）.The parameters of left ventricular structure and function, left ventricular systolic dysfunction, left ventricular diastolic dysfunction, left ventricular hypertrophy and valvular regurgitation were compared.Results The results of echocardiography showed that significant differences existed in echocardiographic parameters among three groups（P<0.05）.Interventricular septum thickness, left ventricular end-diastolic diameter, left ventricular posterior wall thickness, left ventricular mass index and left atrial diameter were significantly lower in control group than those in non-hemodialysis and hemodialysis groups（P<0.05）.The ratio of early and late peak flow velocity of mitral valve and the level of left ventricular ejection fraction were significantly higher in control group than those in non-hemodialysis and hemodialysis groups（P<0.05）;left ventricular mass index and left ventricular posterior wall thickness were significantly lower in non-hemodialysis group than those in hemodialysis group（P<0.05）.No significant inter-group difference existed in the incidence of left ventricular hypertrophy, left ventricular systolic dysfunction or left ventricular diastolic dysfunction（P>0.05）.No significant inter-group difference existed in the incidence of mitral regurgitation, tricuspid regurgitation, aortic regurgitation or pulmonary regurgitation（P>0.05）.The results of tissue Doppler velocity imaging indicated that significant differences existed in early diastolic peak velocity, late diastolic peak velocity and their ratio among three groups（P<0.05）.The early diastolic peak velocity, late diastolic peak velocity and their ratio were significantly lower in hemodialysis group than those in non-hemodialysis and control groups（P<0.05）.Peak early diastolic velocity, late diastolic peak velocity and their ratio were significantly lower in non-hemodialysis group than those in control group（P<0.05）.No significant inter-group difference existed in the incidence of left ventricular diastolic dysfunction（P>0.05）.Conclusions All patients with end-stage renal disease have abnormal left ventricular structure and function, including left ventricular hypertrophy, left ventricular diastolic and systolic dysfunction.Mitral regurgitation is more common than tricuspid regurgitation.And TVI technology is more sensitive to evaluating left atrial lysosis dysfunction than color Doppler echocardiography.